(untitled) (Práxis Educativa, 2017)
Due to the complexities and challenges that teaching is facing nowadays, teachers’ continuous and permanent training is a social need to promote an improvement in education. The different educational reforms driven in the last decades have considered the training and practice dimension of those who teach. It was carried out differently in the way of facing the teachers and their relationship with knowledge. In this article, we intend to display how the political decisions are related to the pedagogies that are developed in the teaching phase. In order to do so, the policies related to the teachers´ training during the 90s and 2000s have been analyzed and explained, together with the main training pedagogic methods of each period. It is acknowledged that the "professional growth" perspective comes of a powerful method to improve and enrich the practice of those who teach, the corresponding training mechanisms are presented to work in those moments. Keywords: Teacher training. Professional growth. Training pedagogy.